Effects of perfluorooctane sulfonate on the hematology and histopathology of juvenile tilapia, Oreochromis niloticus - Billah, Md Baki; Paul, Sudip; Sultana, Sabira; Hasan, Md Jahid; Salam, Md Abdus (Jahangirnagar University Journal of Biological Sciences, 2016)
Perfluorooctane sulfonate (PFOS), a persistent organic pollutant, biologically stable in the environment and bio-accumulate in the tissues of aquatic animals as well as wildlife and humans. The toxicity of perfluorooctane sulfonate were tested at 1, 3 and 5mg/L concentrations on the juvenile tilapia, Oreochromis niloticus after 7, 15, 30, 45 and 60 days of exposure. The hematological parameters revealed that with the increase in concentrations and exposure time the total count of the RBC, WBC and hemoglobin content were significantly (p<0.05) decreased compared to the control. The histopathological examinations showed that PFOS may induce some changes in kidney and liver. The present results demonstrate that additional research may be conducted to identify the mechanism of perfluorooctane sulfonate toxicity Jahangirnagar University J. Biol. Sci. 4(2): 37-45, 2015 (December)